The Application of AJAX Technology in Web-Based Information Systems to Accelerate Decision Making (Case Study: CV. Suka Mandi) - Indra Riyana Rahadjeng; Melyani Handoko; Syabrinildi Syabrinildi; R Jatinurcahyo; Fazhar Sumantri; Didin Solehudin (University of Science and Computer Technology, 2026)
This study evaluates the impact of AJAX technology on managerial decision-making performance in a web-based information system at CV. Suka Mandi. Unlike prior studies that focus primarily on system development, this research incorporates an empirical evaluation using a before–and–after comparison approach. The system was developed using the Waterfall model and integrated with AJAX technology to enhance responsiveness and usability. Data were collected through task completion time measurements, the System Usability Scale (SUS), and user performance evaluations. The results show a significant improvement in operational efficiency. The average task completion time decreased from 15.2 minutes to 8.1 minutes (a 46.7% improvement). The task success rate increased from 68% to 92%, while the error rate decreased from 22% to 8%. The usability evaluation produced a SUS score of 82.5, indicating excellent usability. A paired sample t-test confirmed that the improvements are statistically significant (p < 0.05). These findings demonstrate that AJAX technology not only enhances system interactivity but also significantly improves decision-making speed and accuracy. This study contributes by providing empirical evidence that links asynchronous web technology to improvements in managerial performance.